Design-led upcycling innovation via appropriate technology: A participatory study of women artisan in Jakarta’s circular economy - Adrian, Noel Febry; Wijanarko, Adrian Azhar; Moersid, Rambo Anzhar (Jurnal Desain, 2025)
This study aims to discover how design-oriented community interventions can enable women artisans to transform plastic waste into increased economic value. The study was performed using a participatory methodology with Komunitas Pengrajin Rasyid, a collective of female artisans in Setu, Cipayung, East Jakarta. The program included five phases: socializing, training, technology implementation, mentorship, and sustainability planning. Data collection methodologies include observation, interviews, and documentation. Findings indicate that the implementation of suitable technologies, specifically the gas oven and pressing machine, markedly advancement from earlier single material weaving techniques, demonstrating the potential of material fusion to improve product stability, durability, and aesthetic value. The community developed three novel product prototypes; coasters, tableware holders, and tissue boxes exhibiting improved durability and aesthetic appeal. The introduction of clearer organizational structures, bookkeeping processes, and visual branding improved managerial and marketing capabilities. The results demonstrate that even minor technology and design modifications can yield significant social, economic, and environmental effects, hence enhancing the viability of community-based circular organizations. Future research should focus on longitudinal market testing of the new visual branding to assess its effectiveness, alongside consumer perception studies that evaluate how recycled products are interpreted in different market segments.